IMPLEMENTATION OF THE MERDEKA CURRICULUM TO IMPROVE THE QUALITY OF EDUCATION IN INDONESIA - Nana Suryapermana; Apud; Gilang Kartika Hanum (CV. ADIBA AISHA AMIRA, 2026)
This study aims to describe the implementation of the Merdeka Curriculum in improving the quality of learning in Indonesia. The method used is a literature review examining various relevant sources, such as scientific journals, books, and educational policy documents. The results of the review indicate that the Merdeka Curriculum provides educational institutions and teachers with the flexibility to design learning that is more flexible, contextual, and student-centered. The implementation of this curriculum also encourages the use of diagnostic assessments, differentiated instruction, and projects to strengthen the Pancasila Student Profile, which contribute to the development of students’ competencies and character. However, its implementation still faces a number of challenges, such as teacher readiness, limited infrastructure, and regional disparities. Overall, the Merdeka Curriculum has great potential to improve the quality of learning in Indonesia if it is implemented consistently, collaboratively, and supported by sustainable policies.